Development of Short Tutorial Video Learning Media Instagram in the Motorcycle Chassis Maintenance Courses at Vocational High Schools - Waruwu, Buala Jefriana; Jalinus, Nizwardi; Wulansari, Rizky Ema; Purwanto, Wawan (AI Society & STMIK Indonesia, 2023)
This study uses a Research and Development (R&D) design, with the ASSURE development model. ASSURE development procedures, namely Analyze learner characteristics, State Standards and Objectives, Select Strategies, Technology, Media, and Materials, utilize media and materials, require learner participation, evaluate and revise. The data analysis technique used describes the validity, practicality, and effectiveness of the developed media. The product results obtained from this development research are video tutorial learning media. Based on the results of this study it was concluded that the developed media was declared